Virtual teams challenging human and technical Web 2.0 dimensions. (1st January 2012) - Schumacher, Marinita; Diviné, Marc; Stal-Le Cardinal, Julie; Bocquet, Jean-Claude
Our article responds to the need of a system to build virtual teams that are active in virtual design projects in the area of new product development (NPD). It focuses on a methodology to provide an Aided Virtual Team Building System (Aided VTB System). Requirements of this Aided VTB System are defined and the fulfilment of their demand by appropriate, relevant and recent techniques as solutions that are discussed with help of an enquiry of 34 virtual team leaders. Based on the house of quality, one of the outcomes of the Aided VTB System is to provide recommendations, guidelines and even best practices for virtual teams building.